VLBI observations of the G25.65+1.05 water maser superburst. Issue 3 (14th November 2019) - Burns, R A; Orosz, G; Bayandina, O; Surcis, G; Olech, M; MacLeod, G; Volvach, A; Rudnitskii, G; Hirota, T; Immer, K; Blanchard, J; Marcote, B; et al.
ABSTRACT: This paper reports observations of a 22 GHz water maser 'superburst' in the G25.65+1.05 massive star-forming region, conducted in response to an alert from the Maser Monitoring Organisation (M2O). Very long baseline interferometry (VLBI) observations using the European VLBI Network (EVN) recorded a maser flux density of 1.2 × 10 4 Jy. The superburst was investipgated in the spectral, structural, and temporal domains and its cause was determined to be an increase in maser path length generated by the superposition of multiple maser emitting regions aligning in the line of sight to the observer. This conclusion was based on the location of the bursting maser in the context of the star-forming region, its complex structure, and its rapid onset and decay.